BECOMING A WOMAN:A Liberal Feminist Analysis on the Novel The Reader by Bernhard Schlink - Ati Suryati, - (2011)
This research entitled "Becoming a Woman: A Liberal Feminist Analysis on the Novel The Reader by Bernhard Schlink" aims to explore the ways in which gender roles are subverted through the main female character Hanna Smith. It suggests the subversion of gender roles through the construction in partriarchal society, both male and female needs to adopt traditional gender roles. In this research, the analysis is based on gender theory proposed by Eagly, Wood and Johannesen-Schmidt (2004) and based on liberal feminism theory proposed by Tong (1998). Moreover, this study employs a descriptive qualitative method within textual analysis approach. Later, it is revealed that the evidences in the novel present some values of traditional gender roles and subverted gender roles. In traditional gender roles, as present in the novel, a woman is strongly expected to be passive and demure that she is able to attract man. Furthermore, the interesting point is that the traditional gender roles in The Reader are subverted by the main female character. Hence, it can be concluded that in the novel The Reader, the traditional gender roles are subverted through particular ways, one of which is by joining the army during Nazi time.